Factors Affecting the Competitiveness of Local Products in Bak Bili Leather Weaving Crafts Made from Bili Trees or Bemban Trees in Aceh Besar - Radhiana Radhiana; Kasmaniar Kasmaniar; Mukhdasir Mukhdasir (Universitas Serambi Mekkah, 2022)
The purpose of this study was to determine the factors that influence the competitiveness of local products on Bak Bili woven leather craftsmen made from Bili trees or Bemban trees in Aceh Besar on the marketing performance of MSME products in Aceh Besar. The population of this study consisted of 112 Bak Bili leather woven craftsmen, and the sampling technique using the census method was obtained so that the sample in this study was the same as the total population of 112 people. Sources of data in this study using primary data. The method of data analysis in this study used multiple linear regression analysis. The results showed that simultaneously digital marketing variables, product quality, and price had a significant effect on the competitiveness of local products on Bak Bili woven leather craftsmen made from Bili trees or Bemban trees in Aceh Besar. Then the results of the partial test where the digital marketing variables, product quality and price have a significant effect on the competitiveness of local products. The magnitude of the influence of digital marketing on the competitiveness of local products is 0.392 or 39.2%, and the product quality variable affects the competitiveness of local products. The magnitude of the influence of product quality on the competitiveness of local products is 0.275 or 27.5%, while the price variable also affects the competitiveness of local products, which is 0.228 or 22.8%. Keywords: Digital Marketing, Product Quality, Product Competitiveness, Bak Bili Crafts.